CORPORATE GOVERNANCE INTERNAL DAN KETEPATAN WAKTU LAPORAN KEUANGAN PERUSAHAAN NON KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Rizki, Riri; Husaini, Husaini; P Midiastuty, Pratana (JURNAL FAIRNESS, 2020)
This study aims to examine whether internal corporate governance (the proportion of independence commissioners, board size, independence of audit committees, audit committee financial expertise, audit committee meetings, and audit committee membership) affect the timeliness of financial reporting. This study uses a quantitative approach. Methods of data collection using purposive sampling method. The object of this research is publicly traded non-financial companies listed on the Indonesia Stock Exchange (IDX) for the 2015- 2019 period. The timeliness of financial reporting is measured by Audit Report Lag (ARL) and Management Report Lag (MRL). The data obtained in this study were as many as 113 sample companies. The data analysis method of this research is multiple linear regression. The results of the Audit Lag Report shows that the proportion of independent commissioners, audit committee financial expertise, and audit committee meetings affect the Audit Lag report while the size of the board of commissioners, independent audit committee, and audit committee membership has no effect on the Audit Lag Report. In contrast to the results of Management Report Lag shows that independent audit committees and audit committee meetings affect Management Lag Reports while the proportion of independent commissioners, board size, audit committee financial expertise, and audit committee membership has no effect on Lag Management Reports.